Enhancing productivity through water management in hot arid Rajasthan - Rathore, V. S.; Goyal, R. K.; Yadava, N. D.; Saxena, Anurag; Soni, M. L. (Indian Farming, 2018)
Agriculture is the largest consumer of available water resources. Therefore, better and efficient utilization of water in agriculture is the prime need of the hour. Adopting rainwater harvesting practices like tankas, nadis, micro-catchment for tree establishment and contour vegetative barriers can significantly improve the availability water. The productivity of available water can further be improved by adoption of appropriate choice of crops and cropping which increases on-farm water use efficiency, using more efficient irrigation methods like sprinkler and drip irrigation systems, application of fertilizer and manures, use of efficient mulches by reducing evaporation loss etc.